2004
DOI: 10.1016/j.schres.2003.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Cavum septi pellucidi in first-episode schizophrenia and first-episode affective psychosis: an MRI study

Abstract: A high prevalence of abnormal cavum septi pellucidi (CSP) in schizophrenia may reflect neurodevelopmental abnormalities in midline structures of the brain. The relationship, however, between abnormal CSP and clinical symptoms, and with abnormalities in other limbic structures remains unclear, as does the question of whether a similar abnormality is present in affective psychosis. Seventy-four patients at their first hospitalization, 33 with schizophrenia and 41 with affective (mainly manic) psychosis, and 56 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
54
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 42 publications
7
54
2
Order By: Relevance
“…Nonetheless, the neurodevelopmental abnormalities which are manifest by having a larger CSP may be clinically important for SPD subjects, as suggested by the correlation between the clinical criteria of impairment due to odd speech and number of MRI slices containing a CSP in SPD subjects. Indeed, in schizophrenia, a larger CSP was correlated with thinking disturbances (Kasai et al, 2004), similar to what was shown here.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Nonetheless, the neurodevelopmental abnormalities which are manifest by having a larger CSP may be clinically important for SPD subjects, as suggested by the correlation between the clinical criteria of impairment due to odd speech and number of MRI slices containing a CSP in SPD subjects. Indeed, in schizophrenia, a larger CSP was correlated with thinking disturbances (Kasai et al, 2004), similar to what was shown here.…”
Section: Discussionsupporting
confidence: 88%
“…Such developmental and genetic factors may help explain why there were negative correlations between large CSP and hippocampal volumes (Kwon et al, 1998) and parahippocampal volumes (Kasai et al, 2004) in schizophrenia, but not in SPD. Nonetheless, the neurodevelopmental abnormalities which are manifest by having a larger CSP may be clinically important for SPD subjects, as suggested by the correlation between the clinical criteria of impairment due to odd speech and number of MRI slices containing a CSP in SPD subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complete non-fusion of the two laminae of the septum pellucidum, a phenomenon termed combined CSP and CV, is the most extreme form of CSP. Associations between large CSP and functional psychosis disorders, especially schizophrenia, have been reported [1][2][3][4][5]. We present an unusual case of late-onset catatonia with CSP and CV.…”
Section: Introductionmentioning
confidence: 78%
“…During development, a space exists between the laminae, called the cavum septum pellucidum (CSP); this is filled with cerebrospinal fluid and usually disappears during infancy. However, CSP occasionally persists and may be associated with neurodevelopmental abnormalities of midline and limbic structures [1][2][3]. The cavum vergae (CV) is a normal variant of the septum pellucidum in which there is separation of the laminae with posterior extension to the splenium of the corpus callosum.…”
Section: Introductionmentioning
confidence: 99%